Comparative Effectiveness on Cognitive Asthma Outcomes of the SHARP Academic Asthma Health Education and Counseling Program and a Non‐Academic Program. Issue 6 (22nd August 2015) - Kintner, Eileen; Cook, Gwendolyn; Marti, C. Nathan; Stoddard, Debbie; Gomes, Melissa; Harmon, Phyllis; Van Egeren, Laurie A.
Abstract: Asthma morbidity and mortality is higher among older school‐age children and early adolescents than other age groups across the lifespan. NIH recommended expanding asthma education to schools and community settings to meet cognitive outcomes that have an impact on morbidity and mortality. Guided by the acceptance of asthma model, an evidence‐guided, comprehensive school‐based academic health education and counseling program, Staying Healthy—Asthma Responsible & Prepared ™ (SHARP), was developed. The program complements existing school curricula by integrating biology, psychology, and sociology content with related spelling, math, and reading and writing assignments. Feasibility, benefits, and efficacy have been established. We compared the effectiveness of SHARP to a non‐academic program, Open Airways for Schools, in improving asthma knowledge and reasoning about symptom management. A two‐group, cluster‐randomized, single‐blinded design was used with a sample of 205 students in grades 4–5 with asthma and their caregivers. Schools were matched prior to randomization. The unit of analysis was the student. Certified elementary school teachers delivered the programs during instructional time. Data were collected from student/caregiver dyads at baseline and at 1, 12, and 24 months after the intervention. In multilevel modeling, students enrolled in the academic SHARP program demonstrated significant ( p < .001) improvement in asthma knowledge and reasoning over students enrolled in the non‐academic program. Knowledge advantages were retained at 24 months. Findings support delivery in schools of the SHARP academic health education program for students with asthma. © 2015 Wiley Periodicals, Inc.